Multivariable analysis of 2,4-d herbicide photocatalytic degradation (2011)
The 2,4-D herbicide degradation of TiO2 suspensions in tap water was evaluated under artificial irradiation conditions. The response surface methodology (RSM) was applied to evaluate the effect of variables such as: catalyst concentration, herbicide concentration, pH, and the volumetric flow on the photocatalytic reaction in two kinds of photoreactors: flat plate and tubular reactor. The response variable was the pesticide mineralization expressed as the total organic carbon (TOC) removal percentage of the herbicide after four hours of irradiation. For the treatment carried out in the tubular reactor, the four effects had the same significance on the degradation; whereas for the flat plate reactor, the catalyst concentration and the pH were more significant. The results obtained suggest that the RSM is a suitable technique for obtaining optimal operating parameters of a photocatalytic process with a specific reactor and within a determined range of study.